1995
DOI: 10.1002/j.1460-2075.1995.tb07135.x
|View full text |Cite
|
Sign up to set email alerts
|

TBP mutants defective in activated transcription in vivo.

Abstract: The TATA box binding protein (TBP) plays a central and essential role in transcription initiation. At TATA box‐containing genes transcribed by RNA polymerase II, TBP binds to the promoter and initiates the assembly of a multiprotein preinitiation complex. Several studies have suggested that binding of TBP to the TATA box is an important regulatory step in transcription initiation in vitro. To determine whether TBP is a target of regulatory factors in vivo, we performed a genetic screen in yeast for TBP mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 75 publications
9
86
0
Order By: Relevance
“…The lack of TATA element binding in vitro does not conflict with our conclusion that the TBP mutants directly associate with TATA elements in vivo. In particular, there are a number of TBP derivatives that do not detectably associate with TATA elements in vitro yet are fully competent to support yeast cell viability and transcription in vivo (1,41). This apparent discrepancy is probably due to the fact that TBP association with TATA elements in vivo is stabilized by TAFs and other components of the Pol II machinery (40,44) and hence is not simply due to its inherent DNA-binding affinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of TATA element binding in vitro does not conflict with our conclusion that the TBP mutants directly associate with TATA elements in vivo. In particular, there are a number of TBP derivatives that do not detectably associate with TATA elements in vitro yet are fully competent to support yeast cell viability and transcription in vivo (1,41). This apparent discrepancy is probably due to the fact that TBP association with TATA elements in vivo is stabilized by TAFs and other components of the Pol II machinery (40,44) and hence is not simply due to its inherent DNA-binding affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Direct physical analysis by protein-DNA cross-linking in vivo indicates that, in the vast majority of cases tested, TBP does not associate with core promoters in the absence of a functional activator (40,44). TBP mutants that weaken TATA element binding (1,41) or TFIIA association (4,53) can selectively affect the response to certain activators. Such selective effects on activator-dependent transcription might be related to the observation in vitro that the TATA element is particularly important for supporting multiple rounds of transcription from a preinitiation complex (50,63).…”
mentioning
confidence: 99%
“…Furthermore, npl3-27 exerts a dominant effect on spt15-ts1 cells and not wild-type cells in that expression of exogenous npl3-27 over endogenous wild-type NPL3 causes an mRNA export defect in spt15-ts1 cells. We tested other ts − alleles of spt15 (spt15-328 and spt15-341; Arndt et al 1995) in combination with npl3-27 and found that these alleles also displayed nuclear accumulation of Npl3-27 and mRNA. To determine the specificity of this genetic interaction, we examined strains mutated for RNA Pol II that decrease transcription (rpb1-1, rpb1⌬101, rpb1⌬103), but these strains do not display Npl3-27 or mRNA export defects (data not shown).…”
Section: A Screen For Npl3 Export Factors Identifies Spt15 Which Encmentioning
confidence: 99%
“…MATa and MATa strains used in this study were derived from S. cerevisiae ScTEB652 (MATa ade1 ile leu2-3,112 ura3-52 trp1-HIII his3-D1 MEL1) and FY630 (MATa his4-917d lys2-173R2 leu2D1 ura3-52 trp1D63), respectively (Arndt et al 1995;Blank et al 1997). Details of strain construction will be provided upon request.…”
Section: Strainsmentioning
confidence: 99%